PERBEDAAN HASIL RIAS WAJAH MENGGUNAKAN TEKNIK FACELIFT TAPE VERTIKAL DAN HORIZONTAL PADA MATURE SKIN - Fani Permatasari; Maspiyah; Sri Dwiyanti; Sri Usodoningtyas (Program Studi Pendidikan Tata Rias, 2025)
Makeup techniques are part of life for women regardless of age, differences in skin condition and texture of each woman's face. The purpose of this study was to 1) Determine the results of makeup using the vertical tape facelift technique on mature skin. 2) Determine the results of makeup using the horizontal tape facelift technique on mature skin. 3) Determine the differences in makeup results using the vertical and horizontal tape facelift techniques on mature skin. This research method uses an experimental method with observation sheets taken by 30 respondents. The type of research used is experimental research using the arithmetic mean data analysis technique and the Independent Sample T Test. The results of the study were obtained from the sum of the arithmetic mean values ​​of the five aspects of the vertical tape facelift technique obtained a figure of 2.86 which is classified as sufficient. While the sum of the arithmetic mean values ​​of the five aspects of the horizontal tape facelift technique obtained a figure of 3.67 which is classified as good. In the results of SPSS 25 Independent Sample T Test from both techniques covering all five aspects, the Sig. (2-tailed) figure was obtained less than 0.05 (<0.05). This shows that there is a significant difference in the use of vertical tape facelift and horizontal tape facelift techniques for the results of facial makeup on mature skin from each aspect and overall